Bureaucratic Reform and Business Services in the Special Region of Yogyakarta (Universitas Negeri Semarang, 2023)
This study aims to identify internal and external factors and formulate a strategy for utilizing the Online Single Submission (OSS) system in business licensing services at the Provincial Government of D.I. Yogyakarta. The method used is library research and SWOT analysis. The results show that internal factors, namely the implementation of the OSS system, can streamline time and costs and make it easier for the public to access more transparent and accountable procedures. Meanwhile, external factors in implementing the OSS system were influenced by good cooperation and coordination between the provincial and city/district governments. The strategy for utilizing the OSS system for business licensing services in DIY is optimizing the use and utilization of the OSS system for licensing services, integrating the licensing service system into the Si Cantik Cloud application, strengthening regulations related to the use of the OSS system, increasing the socialization of licensing services through OSS, allocating human resources. Those competent in digital-based public services improve the ball pick-up system in licensing services and control the verification function on permit applicant data.